Hank The Cowdog: The Original Adventures of Hank the Cowdog #1 - Erickson, John R. (the Penguin Group, 1983)
Hank the Cowdog, head of ranch security, is framed for the murder of a chicken and becomes an outlaw with the coyotes
Keywords: Humorous Stories; Mystery and detective stories